Description of Drug Information Services for Hypertension Patients at Drugstore of Abifayrus Clinic FDC (Family Doctor Clinic) Makassar - Megawati, Megawati; Priska, Geby Delin (Jurnal Farmasi Sandi Karsa, 2021)
The research has been done about the description of drug information cervices in hypertensive patients at pharmacies of Abifayruz klinik fdc (family doctor clinic) Makassar.The aim of this research is to know the description of drug information services in hypertensive patients at pharmacies of Abifayruz klinik fdc (family doctor clinic) Makassar. The method of this research is descriptive namely the data obtained by collecting the answers from questionnaires then make tabulation and scoring, and then it will be presented by making a list. Based on the research it can be inferred that hypertensive patient who accepts drug information cervices at pharmacies of Abifayruz klinik fdc, got satisfaction with percentage 74,62%.